2012
DOI: 10.1186/1471-2164-13-130
|View full text |Cite
|
Sign up to set email alerts
|

Gene expression in Atlantic salmon skin in response to infection with the parasitic copepod Lepeophtheirus salmonis, cortisol implant, and their combination

Abstract: BackgroundThe salmon louse is an ectoparasitic copepod that causes major economic losses in the aquaculture industry of Atlantic salmon. This host displays a high level of susceptibility to lice which can be accounted for by several factors including stress. In addition, the parasite itself acts as a potent stressor of the host, and outcomes of infection can depend on biotic and abiotic factors that stimulate production of cortisol. Consequently, examination of responses to infection with this parasite, in add… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

8
64
1

Year Published

2013
2013
2022
2022

Publication Types

Select...
8
2

Relationship

1
9

Authors

Journals

citations
Cited by 81 publications
(73 citation statements)
references
References 74 publications
(89 reference statements)
8
64
1
Order By: Relevance
“…Also Li et al (2012b) recently showed that cell division is increased in rainbow trout eggs containing elevated levels of cortisol. Some of the overrepresented biological processes identified in this study have previously been related to stress, and wound healing and likewise several of these were also found to be affected in salmon skin by cortisol implants (Krasnov et al, 2012).…”
Section: Genes Differentially Expressed In Maternal Stagessupporting
confidence: 64%
“…Also Li et al (2012b) recently showed that cell division is increased in rainbow trout eggs containing elevated levels of cortisol. Some of the overrepresented biological processes identified in this study have previously been related to stress, and wound healing and likewise several of these were also found to be affected in salmon skin by cortisol implants (Krasnov et al, 2012).…”
Section: Genes Differentially Expressed In Maternal Stagessupporting
confidence: 64%
“…A similar effect on the host has been observed in the case of the amoebic parasite Neoparamoeba perurans, the agent of amoebic gill disease, where the same components of the antigen presentation machinery are suppressed in infected tissues (MHC-I and -II, ␤2-microglobulin, TAPBP, and PA28␤) (28). Another pathogen with the capacity to suppress the fish immune system is the salmon louse Lepeophtheirus salmonis (29,30). In this case, the parasite saliva contains biologically active molecules, such as PGE 2 , that suppress the host immune response (31).…”
Section: Discussionmentioning
confidence: 61%
“…Teleost skin is a dynamic organ expressing great variability in physical properties, cell types and hormonal systems involved (reviewed by Rakers et al, 2010;Esteban, 2012). A wide range of susceptibilities to L. salmonis exists among salmonids; coho and pink respond with aggressive inflammation and subsequent rejection of the parasite (Johnson and Albright, 1992;Braden et al, 2012Braden et al, , 2015Sutherland et al, 2011) while in Atlantic, sockeye and chum salmon, there is a delayed or weakened inflammatory response to infection (Skugor et al 2008;Tadiso et al, 2011;Krasnov et al 2012;Braden et al, 2012Braden et al, , 2015Sutherland et al, 2011Sutherland et al, , 2014, which permits heavier parasitic abundance. The study of Holm et al (2014) suggested that a thicker epidermis and larger mucus cell size were not associated with resistance in Atlantic salmon.…”
Section: Introductionmentioning
confidence: 99%